Mutation-Specific Guide RNA for Compound Heterozygous Porphyria On-target Scarless Correction by CRISPR/Cas9 in Stem Cells - Prat, Florence (Stem Cell Reports, 2020)
CRISPR/Cas9 is a promising technology for gene correction. However, the edition is often biallelic, and uncontrolled small insertions and deletions (indels) concomitant to precise correction are created. Mutation-specific guide RNAs were recently tested to correct dominant inherited diseases, sparing the wild-type allele. We tested an original approach to correct compound heterozygous recessive mutations. We compared editing efficiency and genotoxicity by biallelic guide RNA versus mutant allele-specific guide RNA in iPSCs derived from a congenital erythropoietic porphyria patient carrying compound heterozygous mutations resulting in UROS gene invalidation. We obtained UROS function rescue and metabolic correction with both guides with the potential of use for porphyria clinical intervention. However, unlike the biallelic one, the mutant allele-specific guide was free of on-target collateral damage. We recommend this design to avoid genotoxicity and to obtain on-target scarless gene correction for recessive disease with frequent cases of compound heterozygous mutations.